Case based learning in Pancasila education courses - A. Aco Agus; Firman Umar; Manan Sailan; Muhammad Amin (Technium Social Sciences Journal, 2023)
This article discusses the conceptual application of case based learning in the Pancasila Education course. Through conceptual analysis, this article describes the relevance, superiority, and impact of applying case based learning to the Pancasila education subject. Case based learning enables students to respond to and apply Pancasila values in real situations, facilitating deeper understanding and character development based on Pancasila values. This article also discusses challenges and solutions in implementing case based learning. It is hoped that this article will provide conceptual insights for educators in optimizing Pancasila Education.